Thoracic Actinomycosis With Infiltration of the Spine: An Oncological Pitfall. Issue 6 (August 2018) - Ronceray, Leila; Friesenbichler, Waltraud; Hutter, Caroline; Lakatos, Karoly; Krizmanich, Wolfgang; Amann, Gabriele; Boztug, Kaan; Kager, Leo; Mann, Georg; Attarbaschi, Andishe
Abstract : Thoracic actinomycosis with involvement of the vertebral column and chest wall is rare in children and may resemble malignant tumors. A 12-year-old girl was admitted to our clinic having B-symptoms, cachexia, and painful scoliosis (Karnofsky index 20%). Imaging showed a large thoracic left-sided paravertebral tumor with infiltration of the vertebrae, destruction of the chest wall and multiple intrapulmonary nodules. Initially, Ewing sarcoma was suspected and chemotherapy started without previous biopsies. Definite diagnosis of actinomycosis was established later upon histopathologic examination and successfully treated by β-lactam antibiotics. Collectively, this case illustrates that actinomycosis can be an oncological pitfall and possible differential diagnosis.